The road less travelled: Oligopoly and competition policy in general equilibrium - J. Peter Neary (University College Dublin, Department of Economics, 2002)
I review previous approaches to modelling oligopoly in general equilibrium, and propose a new view which in principle overcomes their deficiencies: modelling firms as large in their own market but small in the economy as a whole. Implementing this approach requires a tractable specification of preferences. Dixit-Stiglitz preferences (which imply iso-elastic perceived demand functions) could be used, but continuum-quadratic preferences (which imply linear perceived demand functions) are more convenient. To illustrate their usefulness, I construct a simple closed-economy model of oligopoly in general equilibrium and derive some surprising implications for competition policy.
hdl:10197/1259
Keywords: D50; L13; L40; 330; competition policy; Dixit-Stiglitz preferences; general equilibrium; GOLE (General Oligopolistic Equilibrium); oligopoly; Oligopol; Allgemeines Gleichgewicht; Wettbewerbspolitik; Betriebsgröße; Theorie